The role of libraries in supporting agricultural policy research in Nigeria - Rhoe, Valerie; Oboh, Victor; Shelton, Peter (International Food Policy Research Institute, 2009)
Evidence-based policymaking relies on findings from research and analysis. The availability of information and data is the foundation for sound policy advice, but developing countries lack access to the timely knowledge and data fundamental for drawing reliable conclusions from research. Without a strong information management system, policy arguments are less likely to be effective. Therefore, it’s important to understand the relationship between research findings and decisionmaking. This brief summarizes results from an IFPRI assessment of the capacity of Nigerian libraries within the National Agriculture Research System (NARS) to support agricultural policy research.